Anterolateral thigh osteomyocutaneous flap in head and neck: Lessons learned. Issue 2 (26th June 2021) - Cannady, Steven B.; Mady, Leila J.; Brody, Robert M.; Shimunov, David; Newman, Jason G.; Chalian, Ara C.; Rajasekaran, Karthik A.; Sheth, Neil P.; Shanti, Rabie M.
Abstract: Background: Concerns regarding iatrogenic femur fracture may deter adoption of the anterolateral thigh osteomyocutaneous (ALTO) flap as an alternative reconstructive technique for large composite defects of the head and neck. We describe the evolution of our experience with this flap and the lessons learned in femur management. Methods: Records from a prospective database (July 2009–January 2020) were reviewed to identify patients with composite osseous free tissue reconstructions. Venous thromboembolic events (VTE), femur fracture, estimated blood loss (EBL), procedure time, blood transfusions, and length of stay (days) were compared for ALTO flaps prior to and after the adoption of intramedullary fixation protocol. Results: ALTO represented 10.5% (n = 23) of total osseus (n = 219) flaps. For large composite reconstructions with either ALTO flap, double flap (n = 2), or subscapular mega flaps (n = 14), ALTO flaps were most frequently used (59%, n = 23/59). There were no differences in operative time prior to and after implementation of prophylactic fixation [median (range): 5.4 (1.7–19.2) vs. 5.8 (1.7–15.0), p  = .574]. Additionally, there were no differences in VTE, femur fracture, EBL, blood transfusion, or length of stay ( p  > .05) with adoption of prophylactic intramedullary fixation. Conclusions: The ALTO flap represents a useful tool to consider in the armamentarium of reconstructive options for large through and through defects of the head and neck. In our experience, the ALTO flap is a reasonable alternative to subscapular or double flap reconstructions and especially in the setting of unusable fibular flaps or when bone need exceeds that available from the scapula.